IDENTIFIKASI MODAL SOSIAL TERHADAP POTENSI WISATA RELIGI - Doni Nugroho; Darajati Darajati; Agus Rianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2021)
Kasugengan Kidul Village, Depok District, Cirebon Regency has a magnet in developing the potential of religious tourism, namely Patilasan Nyi Ratu Mas Ayu Gandasari. So many pilgrims who visit Patilasan Nyi Ratu Mas Gandasari. The urgency of this study is to determine the social capital of the potential of religious tourism in the form of Nyi Ratu Mas Gandasari patilasan in Kasugengan Kidul Village. This study uses a qualitative method with a case study approach and uses data collection methods in the form of observation, in-depth interviews (Indefth Interview) and documentation. The data analysis technique used descriptive qualitative research on a case of social capital on the potential of religious tourism in Patilasan Nyi Ratu Mas Ayu Gandari, which is located in Kasugengan Kidul Village, Depok District, Cirebon Regency. The result of the research is that the level of trust of the people in Kasugengan Kidul Village still has the confidence to support the potential of religious tourism in Kasugengan Kidul Village. In addition, the communication carried out by the people of Kasugengan Kidul village is still good, marked by the haul event to visit the great-grandfather of Nyi Ratu Mas Ayu Gandasari. Then the existing norms are still adhered to by the community. so that the identification of social capital on the potential of religious tourism, namely Patilasan Nyi Ratu Mas Ayu Gandasari is still maintained and preserved until now.